Legalitas Transaksi E Commerce Dalam Platfortm Shopee Ditinjau Dalam Kitab Undang-Undang Hukum Perdata (Burgerlijk Wetboek), Undang-Undang Nomor: 8 Tahun 1999 Tentang Perlindungan Konsumen Dan Persfektif Fiqih Muamalah - Hanita Azrica; Seri Mughni Sulubara (Hakim, 2023)
E-commerce is business activities involving consumers, manufactures, service providers and intermediaries using computer networks, namely the internet. E-commerce users are also of various ages, because there are many conveniences when shopping online that only open the desired e-commerce application, select the items purchased and the goods within a few days come as desired. However, behind the convenience of shopping online there must also be weaknesses or disadvantages of shopping online in e-commerce. E-Commerce is the use of the internet and the web for business transactions or more formally E-Commerce is defined as digitally enabled trade transactions between organizations and organizations or with individuals and between individuals and individuals (Sarwono, Jonathan, 2012). The purpose of the research is to find out the legality of e commerce transactions in shopee platfortm reviewed from various existing laws and regulations conventionally and fiqh muamalah. The research method used is empirical legal research, which is research that identifies problems in terms of existing laws in society with the intention of knowing various kinds of symptoms that exist in society (Soekanto, Soerjono, 2010). The findings are regarding the legal validity of the E Commerce agreement in Platfortm Shopee regulated in Article 1320 of the Civil Code (Burgerlijk Wetboek) "namely consensus or agreement of the two parties to bind themselves to each other, proficiency in making agreements, a certain thing or clarity of an item and a halal cause. Regarding the reimbursement of costs, losses and interest due to non-fulfillment of the E Commerce agreement in Platfortm Shopee is regulated in Articles 1243, 1244, and 1245 of the Civil Code). Buying and selling e commerce transactions in fiqh muamalah is the process of exchanging property for property on a mutually willing basis in order to obtain the benefits of the exchange. The law of the permissibility of buying and selling transactions in Islam certainly has a legal basis. The legal basis is the Quran and Hadith.